Beach body work: Australian women's experiences. Issue 3 (4th March 2019) - Field, Candice; Pavlidis, Adele; Pini, Barbara
Abstract: This article examines Australian women's complex relationship with the beach through a focus on affect and on what bodies do. Interviews with ten participants of diverse backgrounds and of different ages reveal that women understand the beach as a mediated and surveilled space where their bodies are foregrounded. In this environment, there is an intersection of women's knowledge of the popular constructions of the archetypal Australian beach body, real women's bodies, and interviewees' experiences of the beach as a place of shame and pride. As a means of managing this affective landscape participants detail a range of bodily strategies enacted prior to going to the beach and once at the beach. This bodily labour demonstrates that for Australian women the beach is a dynamic and complicated site of both leisure and labour.